Integrated nutrient management in Bidi Tobacco and its residual effect on succeeding summer pearl millet - Manju Choudhary; K. M. Gediya; Mahipal Singh Choudhary (Annals of Agricultural Research, 2024)
A field experiment was conducted at Bidi Tobacco Research Station, Anand Agricultural University, Anand to find out “Integrated nutrient management in bidi tobacco and its residual effect on succeeding summer pearl millet” during kharif-rabi and summer season of 2021-22 and 2022-23. The experiment consisted of 9 treatments, replicated four times in randomized block design. Bidi tobacco variety GABTH-2 was considered as kharif-rabi crop and pearl millet variety GHB-1129 was considered as summer residual crop. The experiment results showed significant differences in plant height and leaf width of bidi tobacco at 90 DATP and at harvest with an application of 100% RDN + Equivalent 12.5 t FYM N from poultry manure during years 2021-22, 2022-23 and in pooled analysis. Residual effect of different integrated nutrient management on summer pearl millet failed to exert significant influence on initial plant stand at 20 DAS and at harvest during both individual years and in pooled analysis. The application of treatment T2 (100% RDN + 12.5 t FYM) recorded significantly higher plant height of summer pearl millet at 60 DAS and at harvest during years 2022, 2023 and on pooled basis. An application of 100% RDN + 12.5 t FYM (T2) resulted in a significantly higher number of total tillers per meter row length during the years 2022 and 2023, as well as on pooled basis.